The Impact of integrated marketing communication strategies on customer loyalty: a case of Diamond Trust bank, Nairobi City County- Kenya - Dinesh, H. D. (Strathmore University, 2025)
This study investigated the impact of integrated marketing communication (IMC) strategies on customer loyalty at Diamond Trust Bank (DTB) in Nairobi City County, Kenya. The general objective of the study was to establish the impact of an integrated marketing communication strategy on customer loyalty at DTB in Nairobi City County, Kenya. The specific objectives of the study was to dete1mine how various IMC components, including advertising, sales promotion, personal selling, public relations, and direct marketing, influence customer loyalty, anchored by the Relationship Marketing theory and supported by the Resource Advantage Theory. The study employed descriptive cross-sectional survey design. The unit of analysis was DTB customers across various segments. The study adopted primary data which was collected through structured questionnaires using a five-point Likert scale. The target population was 400 DTB customers and was drawn using Slavin's formula and purposive sampling technique, out of which 364 respondents responded. Data analysis included descriptive and inferential statistics, utilizing tools such as SPSS. The results indicated that all IMC strategies positively influence customer loyalty, with direct marketing having the most significant impact W = 0.243, p = 0.006). Personal selling (~= 0.197, p = 0.014) and advertising W = 0.203, p = 0.016) also showed significant contributions. Public relations and sales promotion had a relatively lower influence but remained crucial components. The findings emphasize the importance of consistent, engaging, and personalized communication in fostering customer loyalty. This research is significant as it offers actionable insights to policymakers in financial institutions to enhance customer retention through strategic IMC practices. Additionally, it contributes to the existing body of knowledge on the role of IMC in fostering customer loyalty, providing a basis for further academic exploration and to marketing practitioners providing insights on how banks can design IMC strategies that are relevant and effective in enhancing customer loyalty.
Full - text undergraduate research project